Engagement or exhaustion? The double-edged sword effect of dual-level transformational leadership on the well-being of young teachers in Chinese secondary schools - Zhuotao Fang; Weixing Zou; Xiangmei Ding (Humanities & Social Sciences Communications)
Abstract Teacher well-being is a critical determinant of educational quality, teacher health, and the holistic development of students. This study investigates the dual-level effects of transformational leadership by school leaders on the well-being of young teachers in Chinese secondary schools. Utilizing the Job Demands-Resources (JD-R) model, we construct a dual-pathway framework to examine how transformational leadership behaviors, perceived by young teachers as either job demands or resources, produce both positive and negative outcomes. Analyzing data from 949 young teachers through multilevel structural equation modeling, the findings reveal that group-focused leadership enhances well-being by improving team adaptability, while individual-focused leadership diminishes well-being by exacerbating role overload. Moreover, task complexity intensifies these effects. This study provides critical insights into balancing the benefits and challenges of transformational leadership, offering significant contributions to the literature on educational leadership and teacher well-being.